Breaches and bridges : German foreign policy in turbulent times - Steinmeier, Frank-Walter 1956- (GIGA distinguished speaker lecture series, 2017)
"Breaches and Bridges : German Foreign Policy in Turbulent Times is an agenda-setting lecture of German Foreign Minister Dr. Frank-Walter Steinmeier. It is accompanied by two essays. The first is an insightful introduction by the first mayor of Hamburg, Olaf Scholz, who reflects on the role of the Hanseatic city in world affairs. The second is a brief contextualisation by Professor Amrita Narlikar, president of the German Institute of Global and Area Studies (GIGA). Narlikar identifies the necessity for a more profound understanding of historical trajectories and political traditions among international negotiating partners, and invokes new forms of leadership and cooperation in global governance. In Dr. Steinmeier's speech, he announces the German candidacy for a non-permanent seat on the UN Security Council and outlines German foreign policy with its cornerstones of peace, justice, innovation and partnership. In a period of global transition and turmoil, the world needs creative and feasible solutions. With its timely analysis, the book provides its readers with just such solutions. It does so by bridging the scholars-practitioners divide. The volume is a valuable reference for the international relations and foreign policy community worldwide. Written in both English and German, the book approaches a broad audience"--Provided by publisher